Mangan Oxide-assisted in Biochar Improvement and Application in Malachite Green Removal - Dina Emilia; Yusuf Mathiinul Hakim; Risfidian Mohadi (Indonesian Journal of Material Research, 2023)
The adsorption features of rice husk biochar (BC) have been improved by structure refinement due to being composited with manganese oxide (MnO). The composite material formed under low energy (temperature) was identified by X-ray Diffraction (XRD), Fourier Transform Infra-red (FTIR), and Brunauer-Emmet-Teller (BET) Surface Area instrumentation. The composite of BC/MnO analysis of XRD was specialized at 9.48° (110) and 31.42° (111). Functional group investigation of FTIR on BC/MnO composite was detected at 349 cm-1 and 401 cm-1 as manganese oxide vibration on biochar. The improvement in specific surface area is evidenced by BET surface area analysis, with the highest result at 96.047 m2/g. Several analyses on the adsorption work concluded that malachite green adsorption on BC/MnO composite follows the pseudo-second-order model and the Freundlich scheme under spontaneous reaction. Additionally, calculation in adsorption parameters resulted in an adsorption maximum capacity of about 79.365 mg/g with regeneration effectiveness up to 48.170% at the final of the seventh cycle.